2007
DOI: 10.1111/j.1440-1819.2007.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the prefrontal cortex during the Trail‐Making Test detected with multichannel near‐infrared spectroscopy

Abstract: The Trail-Making Test (TMT) is a neuropsychological test for evaluating executive function, and the TMT Part B reflects more complex cognitive processes including cognitive set shifting. The prefrontal cortex (PFC) is thought to be involved in these cognitive processes. The purpose of the present paper was to investigate PFC activation during performance of the TMT Part A and Part B using multichannel near-infrared spectroscopy (NIRS). Subjects were 41 healthy right-handed volunteers. The hemodynamic changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 24 publications
7
60
2
Order By: Relevance
“…Our results agree with recent studies by Shibuya-Tayoshi et al 25 and Nakahachi et al, 26 who found a bilateral O 2 Hb increase prefrontally. Interestingly, a widespread, powerful right HHb activation was constantly present in GLM maps throughout the test.…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Our results agree with recent studies by Shibuya-Tayoshi et al 25 and Nakahachi et al, 26 who found a bilateral O 2 Hb increase prefrontally. Interestingly, a widespread, powerful right HHb activation was constantly present in GLM maps throughout the test.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…23 Schreppel et al 24 investigated the effects of interference resolution processes on activation of the PFC in a WM task by means of fNIRS. Shibuya-Tayoshi et al 25 and Nakahachi et al 26 employed fNIRS devices to obtain a mapping of the activation of the PFC during the visuospatial WM Trail Making Test. They reported bilateral activation, primarily in the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…These are the regions that most likely underlie cognitive flexibility during the TMT and are candidate regions underlying the impairment of groups with poor set-shifting abilities. These results are consistent with those presented in these studies [18] [19] [20].…”
Section: Neuroanatomical Correlatessupporting
confidence: 83%
“…NIRS and fMRI are non-invasive methods for measuring brain activity. In studies using fMRI measurements, brain activity was mainly detected in the frontal lobe during TMT performance (Moll et al 2002;Zakzanis et al 2005), and in NIRS measurement, frontal lobe activity was also noted during TMT performance (Shibuya-Tayoshi et al 2007;Shoji et al 2009). A difference in NIRS measurements during TMT performance was noted in a comparison of normal children and children with attention-deficit hyperactivity disorder (Weber et al 2005).…”
mentioning
confidence: 99%